A STUDY OF FACTORS AFFECTING ADOPTION OF PIVOT SPRINKLER IRRIGATION TECHNOLOGY FOR WHEAT CROP PRODUCERS - Mohammed. M. S.,; O. K. Jbara, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was aimed to investigate a model of confirmatory structural validity for indicators of adopting axial sprinkler irrigation technology for wheat producers in Ain Al-Tamr district as the Karbala governorate during the agricultural season (2020-2021) through a number of hypotheses to measure and estimate the latent variables based on the five-point Likert scale to show the behaviors and psychological preferences for a set of phrases the samples targeting of farmers to the most important factor affecting the adoption of pivot sprinkler irrigation technology. The sample consisted of (100) farmers and based on the method confirmatory factor analysis and using the AMOS program. The most important influencing factors were obtained after exceeding the quality of conformity model, as the study proved that technology is of great importance in solving production problems, and social media has a significant impact on the availability of concepts and information about technology and great importance in the dissemination of that technology, and the decrease in water levels in the rivers (Tigris and Euphrates). Climatic changes led to directing the behavior and preferences of producers towards adopting pivot sprinkler irrigation to compensate for the shortage in irrigation water sources. Academic achievement and government support have a significant impact on the producer’s behavior in using modern irrigation methods.